Genetic diversity of Plasmodium falciparum parasite by microsatellite markers after scale-up of insecticide-treated bed nets in western Kenya. (December 2015) - Gatei, Wangeci; Gimnig, John; Hawley, William; Kuile, Feiko; Odero, Christopher; Iriemenam, Nnaemeka; Shah, Monica; Howard, Penelope; Omosun, Yusuf; Terlouw, Dianne; Nahlen, Bernard; Slutsker, Laurence; et al.
Abstract Background An initial study of genetic diversity ofPlasmodium falciparum in Asembo, western Kenya showed that the parasite maintained overall genetic stability 5 years after insecticide-treated bed net (ITN) introduction in 1997. This study investigates further the genetic diversity ofP. falciparum 10 years after initial ITN introduction in the same study area and compares this with two other neighbouring areas, where ITNs were introduced in 1998 (Gem) and 2004 (Karemo). Methods From a cross-sectional survey conducted in 2007, 235 smear-positive blood samples collected from children ≤15-year-old in the original study area and two comparison areas were genotyped employing eight neutral microsatellites. Differences in multiple infections, allele frequency, parasite genetic diversity and parasite population structure between the three areas were assessed. Further, molecular data reported previously (1996 and 2001) were compared to the 2007 results in the original study area Asembo. Results Overall proportion of multiple infections (MA ) declined with time in the original study area Asembo (from 95.9 %-2001 to 87.7 %-2007). In the neighbouring areas, MA was lower in the site where ITNs were introduced in 1998 (Gem 83.7 %) compared to where they were introduced in 2004 (Karemo 96.7 %) in 2007. Overall mean allele count (MAC  ~ 2.65) and overall unbiased heterozygosity (H e  ~ 0.77) remained unchanged in 1996, 2001 and 2007 in Asembo and was the same level across the two neighbouring areas in 2007. Overall parasite population differentiation remained low over time and in the three areas at FST  < 0.04. Both pairwise and multilocus linkage disequilibrium showed limited to no significant association between alleles in Asembo (1996, 2001 and 2007) and between three areas. Conclusions This study showed theP. falciparum high genetic diversity and parasite population resilience on samples collected 10 years apart and in different areas in western Kenya. The results highlight the need for long-term molecular monitoring after implementation and use of combined and intensive prevention and intervention measures in the region.